Kebijakan Implementasi Undang-Undang No 27 Tahun 2022 Pada Kasus Pinjaman Online di Indonesia - Anindya, Aikoo; Sari, Nia Ayu Mayang (Postulat, 2024)
The implementation of Law No. 27 of 2022 on Personal Data Protection in Indonesia’s online lending services has presented new challenges and responsibilities for service providers. While this law provides a robust legal framework to protect consumers' personal data, its practical application remains problematic. Findings show that personal data breaches and unethical debt collection practices continue to occur, highlighting gaps in enforcement. In addition, many service providers still lack full compliance with the law due to insufficient understanding of their obligations, and consumers are often unaware of their data protection rights. The study also identifies the need for stricter supervision and cooperation between regulators, service providers, and other relevant stakeholders to ensure the law is applied effectively. Public education campaigns and consistent enforcement of penalties are essential to strengthen legal protections for consumers. This study recommends periodic evaluations of the law’s implementation, the development of comprehensive monitoring mechanisms, and the enhancement of technological resources to support better oversight of the online lending industry. Strengthening these efforts would contribute to a safer and more reliable fintech ecosystem in Indonesia.